A carta de Quinhamel . The Letter from Quinhamel - Zoettl, Peter Anton (Full Blue, 2008)
Verzio FF Submission Two Guinean students and an anthropologist off-screen. Gina Có is a girl whose mother preferred not to say goodbye before departing, because if anybody else knew she was leaving the country she could have been harmed. Fernando Djú was working as a teacher, but now he’s a pupil. Both of them are in Portugal now to see if they can take a step forward on their way between two worlds.